Integrative medicine - combination of conventional medicine and traditional herbal medicine may find its potential applications in the treatment of certain dermatological and endocrine diseases – review of the literature - Machowiec, Piotr Artur; Maksymowicz, Marcela; Korzeniowska, Anna; Baran, Natalia; Bielak, Adriana; Nowak, Aleksandra; Cywka, Łucja; Szwed, Weronika; Nowak, Alicja; Bogusz, Klaudia (Journal of Education, Health and Sport, 2023)
Introduction and purpose Traditional Chinese herbal medicine is an integral component of a comprehensive healing system known as Traditional Chinese Medicine (TCM). Within TCM, herbs are utilized to rebalance the energy forces of Yin and Yang, which flow through imperceptible channels within the body with the aim of restoring energy equilibrium. It is important to acknowledge that herbs have the potential to exert significant effects on the body comparable to pharmaceutical drugs, and therefore, should be approached with equal caution and respect The aim of the study was to present the current state of knowledge about the potential use of Chinese herbs in the treatment of certain dermatological and endocrine diseases. State of the knowledge Chinese medicine has found application in various diseases and health conditions, both physical and mental. In the studies delving into dermatological diseases, Chinese medicine therapy resulted in a reduction in chronic urticaria activity and psoriasis area severity index. In addition, Chinese herbal medicine (CHM) effectively improved the response rate and reduced the maximum nodule diameter of benign thyroid nodules. Furthermore it was reported that certain Chinese herbs improve the functioning of mitochondria in β-cells contributing to better management of patients with diabetes mellitus. Conclusion Chinese medicine seems to be a valuable supplement to conventional medicine in the treatment of some chronic diseases. Simultaneously, our focus should be on the development of a new wave of pharmaceutical products that guarantee high efficacy and low toxicity conforming to international standards. It is imperative to enhance research in Chinese medicine and advance engineering technologies to ensure the superior quality of TCM preparations.